Peningkatan Hasil Belajar Menulis Kreatif Puisi tentang Peristiwa yang Dialami dengan Menggunakan Media Gambar Siswa Kelas VIII H SMPN 2 Mataram - Utomo, Wasis (Lembaga Yasin AlSys, 2022)
This research was conducted to determine the increase in activity and achievement of class VIII.H students of Mataram 2 Public Middle School in writing creative poetry with the application of media images. This Classroom Action Research uses two cycles with each cycle implementation covering (a) planning action (planning), (b) implementing action (acting), (c) observing (observing), (d) reflecting (reflecting). While the research procedure includes the steps: (1) preparation, (2) initial study/survey, (3) implementation of the cycle, and (4) preparation of reports. The results of data analysis showed that the activities and achievements of class VIII.H SMP Negeri 2 Mataram in writing creative poetry increased. Researchers took action in three cycles, in cycle I it was seen that the percentage of student test scores reached 78%. This shows that students have not fully achieved learning mastery. Whereas in cycle II the percentage of student tests has increased to 94%. This shows that there is an increase in the percentage of student learning completeness. This increase was partly due to an increase in students' motivation and creativity in learning. This indicates an increase in learning outcomes in creative poetry writing material in Indonesian lessons. Although basically the use of media images in learning is not the only method that can be used in Indonesian subjects, this method can help students understand the material for writing creative poetry. However, this also needs to be supported by the willingness of students to study poetry more actively so that it can be applied in everyday life. Based on the results obtained by students in cycle II, this research was declared successful in achieving the research objectives to be achieved.